2020
DOI: 10.1016/j.omtn.2020.08.001
|View full text |Cite
|
Sign up to set email alerts
|

hsa_circ_0003738 Inhibits the Suppressive Function of Tregs by Targeting miR-562/IL-17A and miR-490-5p/IFN-γ Signaling Pathway

Abstract: Dysfunction in the suppressive function of regulatory T cells (Tregs) has been related to the pathogenesis of psoriasis. Accumulating evidence has demonstrated the importance of circular RNAs (circRNAs) in regulating various biological process, such as cell proliferation, apoptosis, etc. However, the role of circR-NAs in modulating the suppressive functions of psoriatic Tregs and the underlying mechanisms have not been investigated. Here, by using circRNA microarray analysis, we discovered four upregulated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…They regulates the proliferation and inflammation of keratinocytes, mesenchymal stem cells (MSCs) and Treg. 13,14,23 However, most researches of circRNAs in psoriasis stayed at the bioinformatic analysis level, the biological function of most circRNAs remains largely unknown. We applied a circRNA microarray to obtain the expression profiles of circRNA in 10 pairs of psoriasis vulgaris lesions and healthy skin tissues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They regulates the proliferation and inflammation of keratinocytes, mesenchymal stem cells (MSCs) and Treg. 13,14,23 However, most researches of circRNAs in psoriasis stayed at the bioinformatic analysis level, the biological function of most circRNAs remains largely unknown. We applied a circRNA microarray to obtain the expression profiles of circRNA in 10 pairs of psoriasis vulgaris lesions and healthy skin tissues.…”
Section: Discussionmentioning
confidence: 99%
“…There are accumulating evidences that many circRNAs have important biological functions, involving in the initiation and development of a variety of diseases, including cancers, autoimmune disease, metabolic disease 10‐12 . In psoriasis, some circRNAs, such as hsa_circ_0003738and hsa_circ_0061012, have been reported to regular the proliferation, migration and invasion of keratinocytes and dysfunction of Tregs 13,14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are highly stable because of their covalently closed ring structure, and some of them are evolutionarily conserved [11]. Furthermore, previous studies reported that circRNAs can exert their biological function as microRNA (miRNA) sponges [12,13] and RNAbinding protein sponges [14] and more controversially, through protein translation [15]. The emerging roles of RNA-RNA crosstalk are further confirmed as our knowledge of noncoding RNAs has expanded.…”
Section: Introductionmentioning
confidence: 96%
“…They are highly stable because of their covalently closed ring structure, and some of them are evolutionarily conserved [ 11 ]. Furthermore, previous studies reported that circRNAs can exert their biological function as microRNA (miRNA) sponges [ 12 , 13 ] and RNA-binding protein sponges [ 14 ] and more controversially, through protein translation [ 15 ]. The emerging roles of RNA-RNA crosstalk are further confirmed as our knowledge of noncoding RNAs has expanded.…”
Section: Introductionmentioning
confidence: 99%